Tigecycline Therapy for Nosocomial Pneumonia due to Carbapenem-Resistant Gram-Negative Bacteria in Critically Ill Patients Who Received Inappropriate Initial Antibiotic Treatment: A Retrospective Case Study - Wu, Xiaomai (Biomed Res Int, 2016)
Background. Nosocomial pneumonia due to carbapenem-resistant Gram-negative bacteria (CRGNB) is a growing concern because treatment options are limited and the mortality rate is high. The effect of tigecycline (TGC) on nosocomial pneumonia due to CRGNB in patients who have received inappropriate initial empiric antibiotic treatment (IIAT) is unclear. Therefore, this study aimed to examine the effect of TGC on nosocomial pneumonia due to CRGNB in critically ill patients who had received IIAT. Methods. A retrospective study was conducted in an adult respiratory intensive care unit. Data were obtained and analyzed for all patients who were treated with TGC ≥ 3 days for microbiologically confirmed nosocomial pneumonia due to CRGNB and had experienced initial antibiotic failure. Clinical and microbiological outcomes were investigated. Results. Thirty-one patients with hospital-acquired pneumonia or ventilator-associated pneumonia were included in the study. The majority of the responsible organisms were carbapenem-resistant Acinetobacter baumannii (67.7%), followed by Klebsiella pneumoniae (16.1%) and Escherichia coli (9.7%). Twenty patients were treated with high-dose TGC therapy (100 mg every 12 h after a 200 mg loading dose), and the others received a standard-dose therapy (50 mg every 12 h after a 100 mg loading dose). The duration of TGC therapy was 14.3 ± 2.8 days. The global clinical cure rate and the microbiological eradication rate were 48.4% and 61.3%, respectively. The overall ICU mortality rate was 45.2%. A higher score on the Acute Physiology and Chronic Health Evaluation II and a longer duration of IIAT were associated with clinical failure. High-dose TGC therapy had a higher clinical success rate [65.0% (13/20) versus 18.2% (2/11), P = 0.023] and a lower ICU mortality rate [30.0% (6/20) versus 72.7% (8/11), P = 0.031] than the standard-dose therapy. Conclusions. TGC, especially a high-dose regimen, might be a justifiable option for critically ill patients with nosocomial pneumonia due to CRGNB who have received IIAT when the options for these patients are limited.